2014
DOI: 10.1111/jcpp.12334
|View full text |Cite
|
Sign up to set email alerts
|

Asperger syndrome in males over two decades: stability and predictors of diagnosis

Abstract: Asperger Syndrome, when considered as an ASD/PDD diagnosis, was fairly stable into adulthood, but there was a significant increase over time in cases no longer meeting criteria for an ASD diagnosis according to the DSM-IV, or AS according to the Gillberg criteria. Cases with a stable diagnosis showed significantly more core ASD symptoms in adolescence/young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 37 publications
9
50
1
2
Order By: Relevance
“…In Helles et al (2015) a thorough analysis of attrition was presented. Of the 100 males at T0, 76 participated at T1 and 50 at T2, 47 participated in all three studies.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Helles et al (2015) a thorough analysis of attrition was presented. Of the 100 males at T0, 76 participated at T1 and 50 at T2, 47 participated in all three studies.…”
Section: Methods Participantsmentioning
confidence: 99%
“…It usually persists into early adulthood, and is still diagnosable according to stringent criteria in about 45 % of the male cases [and in another 25-30 % of male cases as other autism spectrum disorders (ASD)] around 30 years of age (Helles et al 2015). It is currently subsumed under the ASD umbrella of the DSM-5 (APA 2013), where it is coded with the other clinical presentations of ASD, including the category that was previously separately coded as autistic disorder (AD) (APA 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the developmental course of ASD is crucially important for managing life care and planning treatment. However, ASD occurs with many varied developmental paths (Fountain et al 2012;Lord et al 2015), and there is no one consistent life outcome (Fein et al 2013;Helles et al 2015;Steinhausen et al 2016). Variation in ASD developmental course has ranged from typical development in infancy that becomes atypical in early childhood, to marked infant impairment in social and cognitive skills that changes to become optimal adaptive functioning in adulthood (Anderson et al 2014;Fein et al 2013;Fountain et al 2012;Helles et al 2015;Howlin et al 2013;Levy and Perry 2011;Lord et al 2015;Yirmiya and Charman 2010).…”
Section: Do Shared Features Provide Construct Validity For An Asd Spementioning
confidence: 99%
“…Blumberg et al (2015) reported that 13 % of 1607 individuals diagnosed with ASD in childhood no longer met criteria for ASD: 9 % had been initially misdiagnosed and 4 % Blostt heir ASD due to treatment or maturation. Helles et al (2015) found that 24 % of individuals diagnosed initially with Asperger's disorder no longer met criteria for any developmental disorder. However, developmental changes are complex.…”
Section: Predictors Of Asd Outcome Are Variedmentioning
confidence: 99%
See 1 more Smart Citation